Interactions of Novice Researchers with Journal Reviewers: Exploring Recommendations on Academic Writing - Dzul Rachman (Script Journal: Journal of Linguistics and English Teaching, 2023)
Background: Journal reviewers play a crucial role in disseminating research findings, but novice researchers often struggle with their feedback. This study explores how novice researchers engage with journal reviewer feedback.Methodology: This study is part of a larger research project examining novice researchers' publishing attitudes and practices in an English as a foreign language (EFL) setting. A case study approach was employed to gain an in-depth understanding of how novice researchers engage with journal reviewer feedback. Interviews, conducted in Bahasa Indonesia, were the primary data source, supplemented with textual data, including manuscripts and response letters.Findings: Novice researchers engage with feedback behaviorally, affectively, and cognitively. Affective responses vary based on feedback nature and prior experience. They appreciate positive feedback but find rejections frustrating. Personal judgment influences how they value feedback.Conclusion: Novice researchers diligently address all feedback despite emotional fluctuations. This reveals a disconnect between their affective and behavioral domains. The study emphasizes the importance of active engagement with reviewer feedback in the scholarly publication process.Originality: This research fills a gap in understanding novice researchers' interactions with journal reviewer feedback, emphasizing the role of experience and personal judgment. It contributes to the literature on student engagement with feedback in academic writing.